A study on the effects of a Kuppilai (Ennai) oil in the management of chronic wounds - Anpuchelvi, S.; Sritharan, G. (University of Kelaniya, 2017)
Chronic wounds are frequently encountered problems in the present era, mostly due to the complications of trauma or pathological injury and they cause long-term agony to the patients. In the present study, Kuppilai Ennai was prepared and its wound healing potentials were studied on various types of chronic wounds such as Lacerated wounds, Post-operative wounds, Fissures, Burns, Pressure sores, Tropic ulcers, Varicose ulcers and Diabetic ulcers with sugar control. Wound healing effects were studied on 40 patients with chronic wounds (wounds last in more than three weeks). The patients were selected from Herbal Health Care Centre, Kokuvil. The patients were divided into two groups - Group A (Kuppilai Ennai dressing) and Group B (Normal Saline Gauze bandage). The drug was applied topically and patients were studied daily for 30 days and results were analyzed. The wound size, margin and surface, floor/base, colour, itching, burning, pain, smell, discharge and granulation tissue were assessed according to the rating scale. All data based on various parameters were gathered and statistically analyzed in terms of mean (X), standard deviation (S.D.), standard error (S.E.), paired test (t-value). Finally results were incorporated in terms of probability (p) as - p < 0.05 - Insignificant p < 0.01 - Significant p<0.001- Highly Significant. In Chronic Wound the size was decreased up to 69.23% which was statistically highly significant. There was considerable improvement (>80%) in swelling and unhealthy margin. Pain, tenderness, discharge and unhealthy granulation tissue showed moderate effect (between 60 to 70 percent) in the chronic wounds. Therefore, it was concluded that the drug "Kuppilai Ennai" possesses sufficient efficacy in the management of wounds without producing any adverse effects.
Keywords: Kuppilai Ennai; Herbal health care centre; chronic wound